2020
DOI: 10.31594/commagene.710923
|View full text |Cite
|
Sign up to set email alerts
|

Scorpion Fauna and Scorpionism in Zakho Province of Northern Iraq

Abstract: Information regarding scorpion diversity and their envenoming within Iraq in general, and the Northern Iraq in particular, is limited. The number and distribution of scorpion sting cases and some details of the scorpion fauna of Zakho province were reported for the first time in this study. Overall, 2675 scorpion sting cases were reported between 2008 and 2017 consisting of 1362 male victims (51%) and 1313 female (49%). The highest percentage of victims was between 15 and 49 years old and accounted for 59% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The Genus was previously recorded for the first time from Mosul Province as Scorpio maurus (Penther, 1912 andKhalaf, 1962). Pringle (1960) reported that S. maurus is found in Duhok Province, then Al-Azawi (2016) recorded it in Najaf Province also as S. maurus, as well as Kachel (2020) in Zakho Province. While Ahmed (2015) recorded it as a subspecies, Scorpio maurus kruglovi (Birula, 1910) in Erbil Province, Northern Iraq.…”
Section: Distribution In Iraqmentioning
confidence: 99%
See 3 more Smart Citations
“…The Genus was previously recorded for the first time from Mosul Province as Scorpio maurus (Penther, 1912 andKhalaf, 1962). Pringle (1960) reported that S. maurus is found in Duhok Province, then Al-Azawi (2016) recorded it in Najaf Province also as S. maurus, as well as Kachel (2020) in Zakho Province. While Ahmed (2015) recorded it as a subspecies, Scorpio maurus kruglovi (Birula, 1910) in Erbil Province, Northern Iraq.…”
Section: Distribution In Iraqmentioning
confidence: 99%
“…This was confirmed by Al-Azawi (2016) who observed the presence of differences in the measurements taken among individuals of the same species, and recorded S. maurus with a total length 49.02 mm and described Chela as being very wide and the body color was golden to yellow. Whereas Kachel (2020) reported that the color was yellowish brown with dark brown in mesosoma. Ahmed (2015) described S. maurus kruglovi which was found in Erbil city-northern of Iraq to be 6-8 cm in length.…”
Section: Distribution In Iraqmentioning
confidence: 99%
See 2 more Smart Citations
“…According to recent publications, 4162 scorpion stings were recorded in primary health care centres in the Kurdistan Region in 2017 and 2018 ( 9 ). Based on the envenomation epidemiological data of the neighbour countries, Androctonus crassicauda (Olivier, 1807), Androctonus bicolor (Ehrenberg, 1828) and Hemiscorpius lepturus (Peters, 1861) are considered the most dangerous scorpions among the known species in Iraq and they are responsible for the most death cases related to scorpion stings ( 10 11 ).…”
Section: Introductionmentioning
confidence: 99%